LEARNING NAHWU FOR ARABIC STUDENTS IN ISLAMIC COLLEGES: EXPERTS' PERSPECTIVES / ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù†ØÙˆ Ù„Ø·Ù„Ø§Ø¨ ØªØ®ØµØµØ§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙ‰ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø§Ù„Ø®Ø¨Ø±Ø§Ø¡ - Kamaluddin Kamaluddin (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to find out experts’ point of view about the reality of Nahwu learning by Arabic students in Islamic Colleges. Qualitative method was used in this research. The data were collected by interviewing several experts in Arabic language. Results showed that the purpose of Nahwu learning is not only to have the ability in understanding nahwu, but also to apply it in Arabic texts and to communicate; the characteristics of nahwu materials should be easy, simple, realistic, communicative, in stages, cognitive and functional; the method of learning is group work, peer learning, integrative texts, active learning, and communicative method; the media for learning are audio, visual, and audio visual; evaluation is done by implementing nahwu rules to construct and transform sentences, giving syakl on texts, and explaining the position of words in sentences. According to the experts, the ideal nahwu learning will help students to develop the four language skills.